2017
DOI: 10.1080/15459624.2017.1358817
|View full text |Cite
|
Sign up to set email alerts
|

Powered air-purifying respirator use in healthcare: Effects on thermal sensations and comfort

Abstract: Twelve subjects wore an N95 filtering facepiece respirator (N95 FFR), one tight-fitting full facepiece powered air-purifying respirator (PAPR), two loose-fitting PAPRs, and one elastomeric/PAPR hybrid for 1 hr each during treadmill walking at 5.6 km/hr while undergoing physiological and subjective response monitoring. No significant interaction (p ≥ .05) was noted between the five respirators in heart rate, respiratory rate, oxygen saturation, transcutaneous carbon dioxide, and perceptions of breathing effort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 17 publications
4
58
0
Order By: Relevance
“…Other studies have reported increased perception of facial heat and eye dryness in PAPR users. 29,30 In the current study, PAPR users rated their respirators more favorably than N95-FFR users on sense of protection. Similarly, in the study of HCWs familiar with PAPR use during SARS, PAPRs were perceived to be more protective than N95-FFRs.…”
Section: Papr Findingsmentioning
confidence: 58%
“…Other studies have reported increased perception of facial heat and eye dryness in PAPR users. 29,30 In the current study, PAPR users rated their respirators more favorably than N95-FFR users on sense of protection. Similarly, in the study of HCWs familiar with PAPR use during SARS, PAPRs were perceived to be more protective than N95-FFRs.…”
Section: Papr Findingsmentioning
confidence: 58%
“…Results showed that the N95 FFR had a higher tympanic forehead temperature and a higher respirator dead space compared to the other PAPR'S. However, the perception of eye dryness was highest among the tight fitting PAPR, and the two loose-fitting PAPR's had a higher rate of facial heat, but this is thought to be due to exercise induced body heat (Powell, Kim, & Roberge, 2017). A different study conducted by Johnson et al, (2007) evaluated sixteen subjects wearing a tight-fitting PAPR while exercising on a treadmill.…”
Section: Papr Efficiency Resultsmentioning
confidence: 93%
“…Perceived thermal discomfort due to forehead temperature was also a result of the 2017 study by Powell et al. It was also reported that subjects complained of eye dryness as well (Powell et al, 2017).…”
Section: Papr Evaluation With Categorical Datamentioning
confidence: 89%
“…Thermal comfort of the face is much less of an issue with PAPRs as compared to N95 masks due to the battery powered flow of air. However, physical exertion while wearing an elastomeric PAPR can cause an increase in forehead skin temperature, leading to an overall perception of body core thermal discomfort (Powell et al, 2017). The flow of air also can cause an additional perception of discomfort.…”
Section: Papr User Experiencementioning
confidence: 99%
See 1 more Smart Citation